2008
DOI: 10.1093/ndt/gfn083
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of large-vessel arteriopathy in paediatric patients with chronic kidney disease

Abstract: While vascular lesions rapidly progress in CKD and D patients, abolition of the uraemic state by Rtx leads to stabilization or partial regression of CKD-associated arteriopathy. Cumulative dialysis duration and the degree of arterial damage prevalent at the time of grafting are the main determinants of persistent arteriopathy 1 year after Rtx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 24 publications
7
60
3
Order By: Relevance
“…Hypertension is a known independent risk factor for renal disease progression in children [1,3,4]. It is also a risk factor for left ventricular hypertrophy and increased carotid intima-media thickness in children with CKD [5][6][7][8]. There is even early evidence that treatment of hypertension can slow renal progression and reverse cardiovascular changes [4,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a known independent risk factor for renal disease progression in children [1,3,4]. It is also a risk factor for left ventricular hypertrophy and increased carotid intima-media thickness in children with CKD [5][6][7][8]. There is even early evidence that treatment of hypertension can slow renal progression and reverse cardiovascular changes [4,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…When patients on PD are compared to those who have undergone kidney transplant, values are higher for the PD patients, suggesting that the renal replacement process itself promotes development of early atherosclerosis [36]. It has also been reported that CIMT values tend to normalize after kidney transplant [37], indicating that this damage is reversible upon improving renal function and withdrawing the atherosclerosis-promoting stimulus of the renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is difficult to extrapolate outcomes from adult studies. Children starting dialysis rarely have vascular calcification or overt CVD [6,9]. In fact, children are more likely to develop arteriosclerosis with calcification of the tunica media and concentric thickening of the vessel wall, whereas adults with CKD have a combination of intimal and medial calcification, probably compounded by coexisting diabetes, dyslipidaemia and hypertension.…”
Section: Cardiovascular Mortality Among Patients On Pd and Hdmentioning
confidence: 99%
“…Mineral dysregulation with high calcium (Ca), phosphorus (P) and parathyroid hormone (PTH) levels as well as medication dosages of Ca-based P binders and vitamin D compounds have been associated with abnormal vascular measures [3,8,9,11,17] and are considered to be direct evidence of calcification in the vessels [6]. Calcification of the coronary arteries has been reported in 15-30 % of dialysis patients [3,8,11,17] and observed to start as early as the first decade of life.…”
Section: Mineral Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation